Metabolic Phenotyping Predicts Gemcitabine and Cisplatin Chemosensitivity in Patients With Cholangiocarcinoma - Suksawat, Manida; Phetcharaburanin, Jutarop; Klanrit, Poramate; Namwat, Nisana; Khuntikeo, Narong; Titapun, Attapon; Jarearnrat, Apiwat; Vilayhong, Vanlakhone; Sa-ngiamwibool, Prakasit; Techasen, Anchalee; Wangwiwatsin, Arporn; Mahalapbutr, Panupong; et al. (Frontiers in Public Health, 2022)
Gemcitabine and cisplatin serve as appropriate treatments for cholangiocarcinoma (CCA) patients. Our previous study using histoculture drug response assay (HDRA), demonstrated individual response patterns to gemcitabine and cisplatin. The current study aimed to identify predictive biomarkers for gemcitabine and cisplatin sensitivity in tissues and sera from CCA patients using metabolomics. Metabolic signatures of CCA patients were correlated with their HDRA response patterns. The tissue metabolic signatures of CCA patients revealed the inversion of the TCA cycle that is evident with increased levels of citrate and amino acid backbones as TCA cycle intermediates, and glucose which corresponds to cancer stem cell properties. The protein expression levels of cancer stem cell markers were examined on tissues and showed the significantly inverse association with the patients’ responses to cisplatin. Moreover, the elevation of ethanol level was also observed in gemcitabine- and cisplatin-sensitive group. In serum, a lower level of glucose but a higher level of methylguanidine were observed in the gemcitabine-responders as non-invasive predictive biomarker for gemcitabine sensitivity.